2016
DOI: 10.1111/jgh.13238
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance and validity of the subclassification for colorectal laterally spreading tumor granular type

Abstract: This subclassification of LST-G according to the diameters of granules and nodules was both useful for choosing therapeutic strategies in the clinical setting and universally applicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Our study showed LSTs localized mostly in the right colon, similar to those of previous studies in different countries [12][13][14][15][16][17]. LST-G-M was the most common subtype, which contradicted the data from Western countries [3].…”
Section: Discussionsupporting
confidence: 65%
“…Our study showed LSTs localized mostly in the right colon, similar to those of previous studies in different countries [12][13][14][15][16][17]. LST-G-M was the most common subtype, which contradicted the data from Western countries [3].…”
Section: Discussionsupporting
confidence: 65%
“…40 mm. The rarity of invasive carcinoma in patients with LST-G-H lesions has been reported previously 22,25,26) . In contrast, 76% of the LST-G-M lesions were carcinomas, and an increase in tumor diameter was associated with an increased incidence of pT1 carcinoma.…”
Section: Discussionmentioning
confidence: 65%
“…The alternative morphological term “laterally spreading tumor” (LST), proposed by Kudo, is now widely accepted in both Asian and Western countries . Although this is not an official term, the two LST subtypes – granular type (LST‐G) and non‐granular type (LST‐NG) – are significantly associated with frequency of submucosal invasion (LST‐NG 14% vs LST‐G 7%; P < 0.01) . However, the macroscopic type of some lesions is difficult to recognize (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…125 Although this is not an official term, the two LST subtypesgranular type (LST-G) and non-granular type (LST-NG)are significantly associated with frequency of submucosal invasion (LST-NG 14% vs LST-G 7%; P < 0.01). [126][127][128] However, the macroscopic type of some lesions is difficult to recognize (Fig. 4).…”
Section: Level Of Evidence: Ii-2 Level Of Recommendation: Amentioning
confidence: 99%